2008
DOI: 10.1208/s12249-008-9060-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drug Solubility on Polymer Hydration and Drug Dissolution from Polyethylene Oxide (PEO) Matrix Tablets

Abstract: Abstract. The purpose of the study was to investigate the effect of drug solubility on polymer hydration and drug dissolution from modified release matrix tablets of polyethylene oxide (PEO). Different PEO matrix tablets were prepared using acetaminophen (ACE) and ibuprofen (IBU) as study compounds and Polyox ® WSR301 (PEO) as primary hydrophilic matrix polymer. Tablet dissolution was tested using the USP Apparatus II, and the hydration of PEO polymer during dissolution was recorded using a texture analyzer. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 23 publications
2
42
0
1
Order By: Relevance
“…As HME and FDM printing both were performed at temperatures above the melting point of the crystalline PEO and PEG, higher melt viscosity of the matrix polymer would be more effective in limiting the diffusion of PEG and PEO molecules to form large crystalline domains during recrystallization on cooling (post-FDM printing). However despite the fact that PEO is a well-known controlled release matrix excipient which hydrates and swells once it is in contact with aqueous media [39][40][41][42], the limited amount of swelling observed in CME and CMS discs during dissolution, indicated that the dissolution of PEO/PEG in the dispersions is the more dominant process in these blends. The intimate mixing between PEG/PEO and Soluplus and Eudragit E PO may contribute to this observed behavior.…”
Section: Linking Phase Behavior With In Vitro Disintegration and Dissmentioning
confidence: 99%
“…As HME and FDM printing both were performed at temperatures above the melting point of the crystalline PEO and PEG, higher melt viscosity of the matrix polymer would be more effective in limiting the diffusion of PEG and PEO molecules to form large crystalline domains during recrystallization on cooling (post-FDM printing). However despite the fact that PEO is a well-known controlled release matrix excipient which hydrates and swells once it is in contact with aqueous media [39][40][41][42], the limited amount of swelling observed in CME and CMS discs during dissolution, indicated that the dissolution of PEO/PEG in the dispersions is the more dominant process in these blends. The intimate mixing between PEG/PEO and Soluplus and Eudragit E PO may contribute to this observed behavior.…”
Section: Linking Phase Behavior With In Vitro Disintegration and Dissmentioning
confidence: 99%
“…For drug candidates with lower aqueous solubility, the drugrelease rate is dependent mainly on the erosion of the polymeric matrix [33,34] . As demonstrated in Figure 6, about 100% of the tacrolimus is released within 2 h from the commercial capsules.…”
Section: Drug-release Studymentioning
confidence: 99%
“…Release studies show that the complexation of OME with cyclodextrins can enhance drug solubility, and it does facilitate the process of hydration, by allowing continuous water penetration through diffusion and dissolution (43). When ARG was added, the drug release was the largest.…”
Section: Release Studiesmentioning
confidence: 99%